Primary school in Germany: History, fields of activity and future challenges - Renner, Günter (Education and training. National and international tendencies of education and training, 2019)
This article will begin by providing an overview of the eventful history of primary school in Germany. This will include a presentation of the most important periods, from the introduction of primary school as one school for all children in the Weimar Republic to the current developments in the German school system. This is followed by a discussion regarding the central areas of learning within primary schools in Germany and the associated future challenges. This includes educational equity, handling heterogeneity in classrooms and the diversity of children. Then, the article shall consider the connectivity of education from primary school to nursery school and secondary school. The article ends with the presentation of important structural reforms in primary schools and provides an overview of teacher training in German